Missões de Maynas: presença territorial missionária e política de fronteira no Marañón (1638 – 1799) - Santos, Roberta Fernandes dos (2016)
The region now known as Amazonia covers an immense tropical forest with territories divided among nine countries in South America. However, during the colonial period, the Amazon was a border space between the domains of Spain and Portugal and was the scene of territorial disputes. The division of territories between the two Iberian empires was established in the late fifteenth century, by the Treaty of Tordesillas, which gave the appearance that the issue of boundaries was settled. But in practice, the future ownership of those virtual territories would depend on which of the two crowns would apply, effectively, a policy of occupation, economic exploitation and defense of such area. This thesis focuses on the study of the region called Marañón, territory belonging to the Spanish domains. We analyze the missionary project designed for Missions of Maynas, between 1638 and 1799, based on the literature produced and on the documents written by the Jesuits and by the colonial authorities linked to the Marañón. Our intention is to demonstrate how the missionary project was applied in the Missions of Maynas in the period as a politic of frontiers occupation, seeking evidence that this was the only model of settlement proposed to the Marañón and responsible for the consolidation of the Spanish presence in the region